Transmission performance improvement in digital coherent system by suppressing cycle slip using statistical analysis algorithm. Issue 13 (1st June 2013) - Hamaoka, F.; Seki, T.; Matsuda, T.; Naka, A.
Abstract : Cycle slip adversely affects transmission performance in digital coherent systems. Proposed is an algorithm using statistical analysis for suppressing cycle slip in a digital coherent system. The cycle slip suppression effect, transmission performance, and nonlinear tolerance of the proposed algorithm were numerically investigated. The proposed algorithm enables cycle‐slip‐free wavelength division multiplex transmission under the presence of nonlinear optical effect and improves transmission performance.